IMPLEMENTING ROLE-PLAY LEARNING IN A BANK ACCOUNTING COURSE - Nanang Shonhadji (STIE Perbanas Surabaya, 2011)
This paper describes the implementation of Role-Play Learning (RPL) in a bank accounting course at Perbanas Business School. The purpose of this is to enhance students'understanding and learning ability. In this approach information about the individual students, their thoughts, emotions and body language are studied as part of the learning methodologt. The sample studied was made up of 210 students of the bank accounting course in the Perbanas Business School. They were required to use the bank accounting information system in all of their study assignments. The results show that this approach had instigated action-learning and the use of the bank accounting information system had helped students to complete all requirements of their assignments. In addition it was also observed that teacher-students interactions were increased while students'passivity and boredom significantly reduced, Importantly, it also highlights the importance of continuous teacher upgrading.